2013
DOI: 10.1371/journal.pone.0070077
|View full text |Cite|
|
Sign up to set email alerts
|

Lysine-Specific Demethylase 1 (LSD1/KDM1A) Contributes to Colorectal Tumorigenesis via Activation of the Wnt/Β-Catenin Pathway by Down-Regulating Dickkopf-1 (DKK1)

Abstract: We collected paired samples of tumor and adjacent normal colorectal tissues from 22 patients with colorectal carcinoma to compare the differences in the expression of lysine specific demethylase 1 (LSD1) in these two tissues. The results showed that in 19 paired samples (86.4%), LSD1 is more highly expressed in tumor tissue than in normal tissue. To explore the role of LSD1 in colorectal tumorigenesis, we used somatic cell gene targeting to generate an LSD1 knockout (KO) HCT 116 human colorectal cancer cell li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 57 publications
2
46
0
1
Order By: Relevance
“…However, we did not observe any significant change in global methylation levels upon LSD1 inhibitor treatment, suggesting that some unknown mechanism may compensate for the loss of LSD1 demethylase catalytic activity. The result is similar to the study of Huang et al (2013). Although Hunag et al (2013) found that LSD1 contributes to colorectal tumorigenesis via activation of the Wnt/β-catenin pathway by down-regulating Dickkopf-1 (DKK1) and Ding et al (Ding et al 2013) reported that LSD1 promotes metastasis of colon cancer cells by down-regulating the expression of CDH-1, the role of LSD1 in CRC stem cell has not been elucidated.…”
Section: Discussionsupporting
confidence: 80%
“…However, we did not observe any significant change in global methylation levels upon LSD1 inhibitor treatment, suggesting that some unknown mechanism may compensate for the loss of LSD1 demethylase catalytic activity. The result is similar to the study of Huang et al (2013). Although Hunag et al (2013) found that LSD1 contributes to colorectal tumorigenesis via activation of the Wnt/β-catenin pathway by down-regulating Dickkopf-1 (DKK1) and Ding et al (Ding et al 2013) reported that LSD1 promotes metastasis of colon cancer cells by down-regulating the expression of CDH-1, the role of LSD1 in CRC stem cell has not been elucidated.…”
Section: Discussionsupporting
confidence: 80%
“…On the other hand, the 3' domain of HOTAIR maintains LSD1-binding activity (15). LSD1, the first identified demethylase that specifically catalyzes the demethylation of histone H3 lysine 4, is believed to be linked to the transcriptional silencing of tumor-suppressor genes (19)(20)(21)(22). Tsai et al (15) suggested that HOTAIR, as a modular scaffold, is required to target both PRC2 and LSD1 to many promoter elements of genes in order to coordinate chromatin modification for gene repression.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies reported that the expression of Dickkopf-1 (DKK1) was significantly higher in HCT116 cells compared with that in LoVo cells (Yu et al, 2013). DKK1 is one of the key regulators of the Wingless-int (Wnt)/b-catenin signaling pathway, which plays an important role in development and in regulating adult stem cell systems (Huang et al, 2013). Moreover, aberrant regulation of this pathway promotes tumorigenesis of human colorectal cancer (Klaus & Birchmeier, 2008).…”
Section: Discussionmentioning
confidence: 99%